2019
DOI: 10.3233/asy-191568
|View full text |Cite
|
Sign up to set email alerts
|

On parametric Gevrey asymptotics for some nonlinear initial value problems in symmetric complex time variables

Abstract: The asymptotic behavior of a family of singularly perturbed PDEs in two time variables in the complex domain is studied. The appearance of a multilevel Gevrey asymptotics phenomenon in the perturbation parameter is observed. We construct a family of analytic sectorial solutions in which share a common asymptotic expansion at the origin, in different Gevrey levels. Such orders are produced by the action of the two independent time variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(47 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…As a first approach, one is tempted to follow techniques used in the previous works of the authors dealing with singularly perturbed partial differential equations in two complex time variables. On the one hand, the family of equations studied in [13] shows a symmetric role of the time variables in the equation. Although this is the case for (10), in that previous study it holds that the principal part of any of the equations in the family is factorizable as a product of two operators which split the dependence on the time variables.…”
Section: A First Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…As a first approach, one is tempted to follow techniques used in the previous works of the authors dealing with singularly perturbed partial differential equations in two complex time variables. On the one hand, the family of equations studied in [13] shows a symmetric role of the time variables in the equation. Although this is the case for (10), in that previous study it holds that the principal part of any of the equations in the family is factorizable as a product of two operators which split the dependence on the time variables.…”
Section: A First Approachmentioning
confidence: 99%
“…along well chosen halflines L d j ⊂ S j , j = 1, 2, as it was the case in our previous studies [13,14]. Our idea consists on merging this double integral along the product L d 1 × L d 2 into a simple integral along a halfline L d ⊂ C. Geometrically, it consists in a projection on the diagonal part (u, u) ∈ C 2 , u ∈ C of the space C 2 .…”
Section: Second Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In [12], we described a study of a family of equations of the shape (1) which showed a symmetric behaviour with respect to the asymptotic properties of the analytic solutions with respect to both time variables, as initially expected from the generalization of the one-time variable case. More precisely, we proved the following result: given a good covering of C , {E p 1 ,p 2 } 0≤p 1 ≤ς 1 −1 coefficients which are holomorphic functions with respect the perturbation parameter on some neighborhood of the origin, under assumptions (8)- (10).…”
Section: Introductionmentioning
confidence: 85%